The genus Pitardella (Rubiaceae) in Thailand with a description of Pitardella poilanei - Wangwasit, Khanit; Wangwasit, Kamolhathai (Thai Forest Bulletin (Botany), 2025)
A taxonomic account of the genus Pitardella in Thailand, with P. poilanei the sole species, is presented. Description, photographs and taxonomic notes are provided based on newly collected materials; in addition, a lectotype for P. poilanei is designated.